2020
DOI: 10.1167/tvst.9.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Modulation Therapy—A Stem Cell Therapy Without Stem Cells for the Treatment of Severe Ocular Burns

Abstract: Ocular injuries caused by chemical and thermal burns are often unmanageable and frequently result in disfigurement, corneal haze/opacification, and vision loss. Currently, a considerable number of surgical and pharmacological approaches are available to treat such injuries at either an acute or a chronic stage. However, these existing interventions are mainly directed at (and limited to) suppressing corneal inflammation and neovascularization while promoting re-epithelialization. Reconstruction of the ocular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Thus, aberrant stiffening of the limbus promotes excessive differentiation of LESCs, thereafter resulting in stem cell deficiency, corneal opacification, and vision loss ( Nowell et al, 2016 ). Collagenase treatment could rescue these alterations by softening the matrix, leading to inactivation of YAP signaling and inhibition of LESC differentiation ( Figure 1B ) ( Gouveia and Connon 2020 ). This research highlights the potential of regulating LESC function and corneal epithelial tissue regeneration by controlling tissue biomechanics and mechanotransduction.…”
Section: The Impact Of Mechanical Cues From the Extracellular Matrixmentioning
confidence: 99%
“…Thus, aberrant stiffening of the limbus promotes excessive differentiation of LESCs, thereafter resulting in stem cell deficiency, corneal opacification, and vision loss ( Nowell et al, 2016 ). Collagenase treatment could rescue these alterations by softening the matrix, leading to inactivation of YAP signaling and inhibition of LESC differentiation ( Figure 1B ) ( Gouveia and Connon 2020 ). This research highlights the potential of regulating LESC function and corneal epithelial tissue regeneration by controlling tissue biomechanics and mechanotransduction.…”
Section: The Impact Of Mechanical Cues From the Extracellular Matrixmentioning
confidence: 99%
“…The relative increase of Young's modulus 14 days postburn could be due to the development of chronic inflammation, neovascularization, and, most importantly, the increased fibrotic response associated with the wound healing process [16,56]. During the early repair phase (i.e., 8-20 days postburn) of the wound healing process, the normal structural elements of the stroma are replaced by excessive accumulation of the ECM matrix and distorted distribution of collagen fibers, resulting in fibrosis which is characterized by scarring and stiffening of tissue [2,16,56,60]. Different from the results of the current study, uniaxial tensile testing on porcine corneas demonstrated weakening of alkali-lesioned and cultured tissues compared with their healthy and fresh counterparts on day 7 post-AB [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to alkali compounds causes the saponification of fatty acids in cell membranes and the destruction of the extracellular matrix (ECM) components. Depending on the dose and duration of exposure, such penetrating burns result in more significant epithelial disruption and destruction of the structure of the underlying stroma, which governs core corneal functions, including transparency, avascularity, shape, and mechanical strength [1][2][3][4]. These functions are attributed to the composition and structure of its ECM, which is mainly comprised of collagen fibrils that are regularly spaced apart by proteoglycans [5,6].…”
mentioning
confidence: 99%
“…Deng et al 61 discuss an emerging therapeutic approach involving extracellular vesicles derived from mesenchymal stem cells, in particular, stromal stem cells, for corneal function and vision restoration. Gouveia and Connon 62 present an approach to biomechanical modulation therapy that promotes the regeneration of corneal/ocular tissues via restoration of the limbal stem cell niche. McDaniel et al 63 illustrate the potential of an ocular wound chamber for treating corneal surface injuries and infections, and Tripathi et al 64 highlight the importance of developing novel, multimodal, non-steroidal topical eye drops capable of utilizing concomitant mechanisms of action in preventing and treating corneal damages caused by toxic chemicals such as mustard gas in vivo.…”
Section: Future Directions For Treatment Of Corneal Chemotoxicitymentioning
confidence: 99%